Palladium‐Catalyzed Synthesis of Alkylcarbazoles and Their Identification in Petroleum and Source Rocks. Issue 22 (8th June 2022) - Theumer, Gabriele; Bauer, Ingmar; Jäger, Anne; Schwark, Lorenz; Knölker, Hans‐Joachim
Abstract: We describe the synthesis of seven C2 ‐alkylcarbazoles via a sequence of Buchwald–Hartwig coupling of arylamines with aryl halides followed by oxidative cyclization of the resulting diarylamines. Methyl groups at the positions 4 and 5 were introduced by taking advantage of the ortho ‐directed palladation of meta ‐pivaloyloxy‐substituted diarylamines and subsequent conversion of the pivaloyloxy to methyl groups through Stille coupling of intermediate triflates. The obtained ethyl‐ and dimethylcarbazoles served as analytical standards for their identification in petroleum samples and source rocks. Abstract : Petroleum samples from different sources were investigated and it was found that they show a characteristic GC‐MS pattern of C2 ‐alkylcarbazoles. The ethyl‐ and dimethylcarbazoles used as analytical standards have been prepared by palladium‐catalyzed synthesis.